2019
DOI: 10.1038/s41419-019-1478-4
|View full text |Cite|
|
Sign up to set email alerts
|

Keratinocyte differentiation promotes ER stress-dependent lysosome biogenesis

Abstract: Keratinocytes maintain epidermal integrity through cellular differentiation. This process enhances intraorganelle digestion in keratinocytes to sustain nutritional and calcium-ionic stresses observed in upper skin layers. However, the molecular mechanisms governing keratinocyte differentiation and concomitant increase in lysosomal function is poorly understood. Here, by using primary neonatal human epidermal keratinocytes, we identified the molecular link between signaling pathways and cellular differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 63 publications
6
55
0
Order By: Relevance
“…Although corneal basal epithelial cells also have lysosomes, lysosomal biogenesis is increased in differentiating cells of the epithelium where lysosomes function in autophagy to degrade organelles in cells before the cells are sloughed off. 28 The large dynamic range of expression in LAMP1 made it difficult to quantify changes in LAMP1 expression over time. By analyzing LAMP1 in n = 5 male and n = 5 female corneas, we could confirm that LAMP1 is expressed at significantly higher levels at ZT 22.5 than at any other time point ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although corneal basal epithelial cells also have lysosomes, lysosomal biogenesis is increased in differentiating cells of the epithelium where lysosomes function in autophagy to degrade organelles in cells before the cells are sloughed off. 28 The large dynamic range of expression in LAMP1 made it difficult to quantify changes in LAMP1 expression over time. By analyzing LAMP1 in n = 5 male and n = 5 female corneas, we could confirm that LAMP1 is expressed at significantly higher levels at ZT 22.5 than at any other time point ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Factors that influence mitochondrial conditions, such as ROS and ER stress, may participate in preparing for cornification. Indeed, several previous studies showed the importance of ROS and ER stress in keratinocyte differentiation [61][62][63][64] .…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports the notion that mitochondria are partly degraded by autophagy in granular cells before the start of morphological change. It is debatable, however, whether autophagy itself is essential for cornification in the physiological epidermis 10,[55][56][57][58][59][60][61] . Factors that influence mitochondrial conditions, such as ROS and ER stress, may participate in preparing for cornification.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the gradient of calcium that spans the epidermis regulates gradual differentiation across epidermal sublayers (Figure 1; Hennings et al, 1989; also reviewed in Bikle et al, 2012). Based on this fact, many in vitro studies utilizing human primary keratinocytes use calcium to trigger the differentiation process (Hennings et al, 1989;Tu et al, 2007Tu et al, , 2012Toufighi et al, 2015;Mahanty et al, 2019;reviewed in Bikle et al, 2012;Elsholz et al, 2014). Note that the epidermal sublayers having eLBs are only observed in vivo or in three-dimensional (3D) skin models (Pillai et al, 1988;Boyce and Williams, 1993;Fartasch and Ponec, 1994).…”
Section: Epidermal Structure Homeostasis and The Skin Barriermentioning
confidence: 99%